Inflation Targeting as a Framework for Monetary Policy - Debelle, Guy (Economic Issues; Economic Issues ;, 1998)
Inflation distorts prices, erodes savings, discourages investment, stimulates capital flight, inhibits growth, and makes economic planning a nightmare. During the past decade, several advanced economies have taken a new approach to the age-old problem of controlling inflation through monetary policy known as "inflation targeting." This pamphlet explains the requirements of putting the new policy in place, the experience of the countries that have tried it, and whether it has applicability to developing countries.